Energy efficiency in buildings by using evolutionary algorithms: an approach to provide efficiency choices to the consumer, considering the rebound effect - Santos, Ricardo (2019)
Energy efficiency can be achieved, by making optimal choices of household appliances, based on specific rules for consumption and use. However, it's not always possible to achieve good solutions, since in general, an efficient equipment, with an economic consumption savings during his life cycle, is usually an expensive one, with a high initial investment. Additionally, the interaction of these choices, associated with consumer behavior, could lead toward to efficient losses during the lifecycle of the equipment, and then to a situation of indirect rebound effect. In this work, it is presented an approach, applied to the residential buildings, by using evolutionary algorithms to support consumer decisions. The approach presented here, could promote energy efficiency by providing the consumer with several optimal and feasible solutions, and at the same time, with information about the impact of his choices made on future.